Hubungan antara kelimpahan plankton dengan hasil tangkapan ikan tuna madidihang (Thunnus albacares) di Perairan Kepulauan Banda, Ambon - Umi Chodriyah; Bram Setyadji (Depik, 2017)
Study related to plankton community in the Banda Sea and its adjacent sea has been conducted by several authors; However, t information on the relationships between of plankton abundance and catches volume of yellowfin tuna Thunnus albacares has been never been examined. Therefore, the objective of this study was to analyze the relationships between plankton abundance and catch volume of yellowfin tuna in Banda Sea Waters, Ambon. The result showed that the highest abundance of phytoplankton (59.259 cell/m3) was found at station 10, around Ambon, Seram and Haruku Island which located in the waters between many river runoffs. While, the highest abundance of zooplankton was 5,483 ind/m3, located around Ambelau Island. Both diversity (H') and evenness (E) index of phytoplankton were at the medium level, and there were no dominant species in this observation. Based on visual observation of remote sensing data, there was an indication of a relationship between the area with high concentration of chlorophyll-a (high phytoplankton biomass) with CPUE value of yellowfin tuna.Studi mengenai komunitas plankton di Laut Banda dan sekitarnya telah banyak dilakukan, akan tetapi telaah hubungan antara kelimpahan dan distribusi plankton dengan aspek perikanan belum banyak dibahas. Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara kelimpahan dan distribusi dari komunitas plankton dengan perikanan tuna di Perairan Kepulauan Banda. Kelimpahan fitoplankton tertinggi terdapat pada stasiun 10 yang terletak di daerah antara pulau Ambon, Seram dan Haruku (59.259 sel/m3) yang mempunyai akses ke muara-muara sungai di sekitarnya. Sedangkan kelimpahan zooplankton tertinggi terletak di sekitar Pulau Ambelau (stasiun 3), yakni 5.483 ind/m3. Tingkat indeks keanekaragaman (H) fitoplankton sedang, indek keseragaman (E) rendah hingga sedang, dan tidak ditemukan jenis tertentu yang dominan. Berdasarkan pengamatan visual data penginderaan jauh memberikan indikasi adanya keterkaitan antara daerah dengan konsentrasi klorofil-a yang tinggi (biomassa fitoplankton tinggi) dengan hasil tangkapan per unit upaya penangkapan tuna madidihang.